Combined Factor V and Factor VIII Deficiency: A Case Report: - Shahverdi, Ehsan; Abolghasemi, Hassan; Dolatimehr, Fardin; Beheshtian, Sara; Chaeichi, Shima Melatshahi; Masoumi, Avishan (Galen Medical Journal, 2016)
Background: Combined factor V and factor VIII deficiency (F5F8D, OMIM 227300) is a rare autosomal recessive bleeding disorder. It seems more common among Jews and Iranians, particularly in regions with frequent consanguineous marriages. Case Report: We describe a 5-yearold girl born out of consanguineous marriage with a complaint of prolonged bleeding after dental extraction. There were no history of spontaneous bleeding and other coagulation defect symptoms. Conclusion: In frequent consanguineous marriage regions, inherited deficiency of factor V and VIII should be considered in patients with coagulation defect symptoms.[GMJ. 2016;5(1):42-44]